Self-Criticism To Arab And Muslim Intellectuals - Fachrizal Halim (Universitas Islam Negeri Mataram, 2007)
Contemporary Arab Thought: Studies in Post-1967 Arab Intellectual Historyis written as a self-criticism addressed to Arab and Muslim intellectuals, especially those who reside in the West. The Arab intellectuals or Muslims alike, who have received Western education and have decided to live in Western countries in the first half of twentieth century, have actually benefited from their modern secular education. The liberalization of U.S. immigration laws in 1965 for non-European immigrants has even enlarged the number of Arabs and Muslims who have trained in the best institutions in the U.S. By the dawn of the twentieth century, the number of Arab intellectuals who reside in the West is estimated to double, as the result of the emergence of a second generation. However, the large number of educated Arab people does not always fulfill the promise of transformation of the social conditions of the Arab World. Far from being ‘organic intellectuals’, to use Gramsci’s favorite term, who would transform Arab societies from imperialism and Western hegemony, and the impact of dependency on the so called ‘globalization,’ most Arab thinkers in the West as well as the elite in the Arab world have been party to Western capitalist interests which aim to control the Arab World. By no means denigrating the works of Isma‘il Raji al-Faruqi, Edward Said, Ghada Hashem Talhami, Halim Barakat, or the feminist Leila Ahmad, to mention some brilliant Arab intellectuals, most Arab thinkers in the West seem to have forgotten the social conditions of the Arab world that have been in acute crisis since the mid nineteenth century or from the time colonialism stepped into the Arab world. Pseudo modernization—to say that there has never been any modernization as it emerged from the middle class as in Europe, but was initiated mainly by the elites—has kept Arab intellectuals in the West completely in the dark and unable to offer radical solution to the crises of the Arab world. As an Arab intellectual living in the West, the author, Ibrahim M. Abu-Rabi`, invites his fellow Muslims, or more generally Arab intellectuals to answer the very basic question: why have we failed to produce a critical and constructive Islamic thinking or knowledge to wrestle with the multitude of problems facing Muslims in any of the world’s advanced capitalist societies (xiii)?